City beautification through corporate social responsibility landscape branding in enhancing urban landscape identity in Kisumu City, Kenya - Edwin Koyoo (Acta Structilia)
City identity and branding have traditionally been shaped by iconic architecture, including monumental buildings and landmarks. However, recent studies have begun to explore city branding through corporate social responsibility (CSR) initiatives, particularly from a landscape perspective. There is limited research, particularly in the Global South, examining the role of CSR in the enhancement of open green spaces and its contribution to shaping urban landscape identity. This study investigates CSR-driven beautification projects in Kisumu City, Kenya, where corporate-funded initiatives have sought to improve urban landscapes through the landscaping of road islands and roundabouts, alongside broader urban renewal efforts. The article aims to document the spatial attributes of these CSR projects; assess their current status in terms of cleanliness, safety, and maintenance, as well as identify the challenges faced in implementing CSR-driven beautification efforts. The aim of these projects is not only to promote the city’s unique urban identity, but also to enhance the corporate image through landscape branding. A qualitative research methodology is employed, involving field observations, GIS mapping, and photography, complemented by purposive interviews. The findings reveal not only diverse landscape designs, including water features and sculptures, but also highlight significant issues with upkeep, safety concerns from street urchins, and the overall deterioration of some sites. These results are valuable for policymakers in city governments and corporations involved in CSR projects, offering insights into how such initiatives can better contribute to urban landscape identity, city branding, and the sustainability of urban beautification efforts.